THE IMAGE OF AN EFFECTIVE SERGEANT OF THE NATIONAL GUARD OF UKRAINE - Matsegora, Yanina; Kolesnichenko, Oleksandr; Batsamut, Volodymyr; Leshchenko, Serhii (Honor and Law, 2023)
The role of sergeants in military units is difficult to overestimate. Quite often, sergeants are more experienced than their immediate commanders ‒ junior officers. The reform of the sergeant's staff contributed to the formation in the minds of servicemen of the image of a sergeant as close as possible to the requirements of NATO, intensive participation in military operations and their provision put forward the requirements for the sergeant's reliability ‒ his ability to perform the task under any conditions, his loyalty to his comrades in arms ‒ to the leading positions and the Motherland. However, servicemen who perform tasks in the zone of direct combat conflict rate more highly the necessary characteristics of a sergeant, which ensure effective teamwork. In support units, sergeants are expected to have the most human-centered approach to personnel. The results of the study of the perception of the image of an effective sergeant in combat units and support units of the National Guard of Ukraine are presented. Reasoned groups of characteristics that determine the effectiveness of sergeants, as assessed by servicemen with intensive combat experience and rear support experience. It is proved that the structure of the characteristics of the sergeants of combat units and rear support units of the National Guard of Ukraine has similar features that allow us to describe them as effective managers who are able to organize the work of the unit and achieve the set goals in the existing circumstances, taking into account the characteristics of each of their subordinates and the available resources for their motivation. However, it is expected from the sergeants of combat units that they will be able to activate, so to speak, the "zone of immediate development", contribute to raising the level of training of subordinates to a qualitatively new level, and as motivation they will use not only personal needs, but also stimulators belonging to to semantic regulation, go beyond the boundaries of an individual personality.